The wellbeing of children in emergency housing motels : service providers’ perspective : Master of Public Health, Massey University - Williams, Bernadine (Massey University, 2023)
Children who are homeless experience compounding social vulnerabilities including unhealthy and/or insecure housing, food insecurity and disruptions to education and medical care. Homeless children require appropriate, collaborative and holistic interventions to ensure wellbeing. Despite extensive national and international research, child homelessness continues to persist (Bornman & Mitchell, 2020). The New Zealand Government defines child homelessness as those children residing in “temporary accommodation” and spends a significant amount on emergency housing every financial quarter; with the Waikato Region spending more than other regions in New Zealand to house children and their whānau in emergency housing motels. This qualitative research used an intersectional approach to investigate the wellbeing of children in emergency housing motels in Hamilton City, Waikato. The aim of the research was to identify what service providers in Hamilton provide in terms of health interventions and wellbeing measures for children residing in emergency housing motels, including barriers and enablers to providing services. The perspectives of service providers supporting children who are homeless were explored through in-depth interviews. Inquiry was guided by the following research questions (1) how are children who reside in emergency housing motels in Hamilton currently supported? (2) are there social factors which strengthen or undermine these support services? and (3) are there opportunities for collaboration between various stakeholders to deliver services at emergency housing motels? Thematic analysis was used to inductively identify themes to form the research findings. The findings identified that living conditions, personal safety, barriers between service providers and whānau, and collaboration hinder the wellbeing of children residing in emergency housing motels and that it is important to support whānau through strengths-based education. The responses of service providers to children residing in emergency housing is complex and may inadvertently lead to the compounding of disadvantage. Service systems require a collaborative approach to improve the living conditions and personal safety of children, and to promote co-ordination between services in order to support the wellbeing of children residing in emergency housing motels. Aotearoa New Zealand can learn from international models such as those used in Finland to address and minimise homelessness through purpose-built housing with proactive services, such as health and social services located within the residence. It is recommended that further research be conducted to understand the first-person experiences of whānau, and children living in emergency housing and explore how they perceive the influence of various social support services on their wellbeing.
Keywords: 420601 Community child health